2020
DOI: 10.1534/genetics.120.303190
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Hsp70 Cochaperone Ydj1 Regulates Functional Distinction of Ssa Hsp70s in the Hsp90 Chaperoning Pathway

Abstract: Heat-shock protein (Hsp) 90 assists in the folding of diverse sets of client proteins including kinases and growth hormone receptors. Hsp70 plays a major role in many Hsp90 functions by interacting and modulating conformation of its substrates before being transferred to Hsp90s for final maturation. Each eukaryote contains multiple members of the Hsp70 family. However, the role of different Hsp70 isoforms in Hsp90 chaperoning actions remains unknown. Using v-Src as an Hsp90 substrate, we examined the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Thus, the presence of specific JDPs determines the fate of specific target substrates. Accordingly, a yeast-based study recently showed how the HSP70 homologue Ssa2 has significantly larger affinity for Ydj1 than its paralogue Ssa4, which may be the reason for the pronounced ability of Ssa2 to assist maturation of Hsp90 substrates [161]. Since JDPs regulate which substrates are presented to HSP70, they are essential components of the chaperone network.…”
Section: Regulation Of Chaperone Activitymentioning
confidence: 99%
“…Thus, the presence of specific JDPs determines the fate of specific target substrates. Accordingly, a yeast-based study recently showed how the HSP70 homologue Ssa2 has significantly larger affinity for Ydj1 than its paralogue Ssa4, which may be the reason for the pronounced ability of Ssa2 to assist maturation of Hsp90 substrates [161]. Since JDPs regulate which substrates are presented to HSP70, they are essential components of the chaperone network.…”
Section: Regulation Of Chaperone Activitymentioning
confidence: 99%
“…Ssa1p is a chaperon in the cytoplasm, involved in the protein folding and trafficking [47]. Ydj1p is a cochaperone protein of Ssa1p and participates in the activity of Ssa1p [48]. At present, there are still no reports on their applications in improving protein folding.…”
Section: The Effects Of Chaperones On Pinene Productionmentioning
confidence: 99%
“…Studies in yeast and mammals indicate that Hsp40s bind upstream of Hsp70s modulating their specificity [ 89 , 90 ]. In yeast, cytosolic Hsp40 chaperones such as Sis1, Xdj1, and Ydj1 were shown to recognize mitochondrial precursors and assist recruitment of Hsp70 (Ssa) chaperones [ 79 , 80 , 91 , 92 , 93 , 94 ].…”
Section: Molecular Chaperones Are Essential To Run the Post-translational Importmentioning
confidence: 99%
“…Multiple studies demonstrated the importance of the most abundant yeast Hsp40 Ydj1 as a docking agent for mitochondrial-targeted proteins [ 80 , 91 , 92 , 93 ]. The YDJ1 gene deletion affects both mitochondrial and ER targeting, causing severe growth defects [ 80 ].…”
Section: Molecular Chaperones Are Essential To Run the Post-translational Importmentioning
confidence: 99%